The Relationship Between Body Mass Index and Foot Oxygen Saturation with Peripheral Neuropathy in Patients with Diabetes Mellitus - Anggraeni, Novita Reza; Sukarmin, Sukarmin; Yulisetyaningrum, Yulisetyaningrum (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to analyze the relationship between body mass index (BMI) and foot oxygen saturation with the incidence of peripheral neuropathy in patients with diabetes mellitus, considering that this complication is common and can be influenced by various risk factors. Research Method: This quantitative study used a cross-sectional design at the Gribig Kudus Community Health Center. A sample of 82 respondents was selected from 103 patients with diabetes mellitus using the Slovin formula and a purposive sampling technique, based on inclusion and exclusion criteria. The instruments included the Semmes-Weinstein Monofilament Test for diagnosing peripheral neuropathy, a scale and stature meter for measuring BMI, and a pulse oximeter for measuring oxygen saturation in the feet. Univariate analysis was conducted to describe the characteristics, and bivariate analysis was performed using the Spearman rank correlation test. Results and Discussion: The results of the study indicate a relationship between BMI and foot oxygen saturation with the incidence of peripheral neuropathy in patients with diabetes mellitus. A high BMI and decreased oxygen saturation in the feet contribute to an increased risk of peripheral neuropathy through mechanisms involving circulatory disorders and microvascular damage. Implications: These findings can serve as a basis for healthcare professionals to implement preventive interventions and early management of peripheral neuropathy complications through weight control, monitoring of extremity oxygen saturation, and education for patients with diabetes mellitus.